Persistent Pulmonary Hypertension of Non Cardiac Cause in a Neonatal Intensive Care Unit - Gustavo Rocha; Maria João Baptista; Hercília Guimarães (Pulmonary Medicine)
Parenchymal lung diseases are the main cause of persistent pulmonary hypertension of the newborn (PPHN). We aimed to assess the non cardiac conditions associated to PPHN in the newborn and the survival rate over the last 15 years, at our center. A retrospective chart review of the neonates admitted for PPHN from 1996 to 2010 was performed. New therapies were introduced in 2003, and the survival rates between two periods (1996–2002 and 2003–2010) were compared. Out of 6750 newborns, 78 (1.1%) had the diagnosis of PPHN of non cardiac cause. The most prevalent causes were associated to pulmonary hypoplasia (30.7%), infection (24.3%), and aspiration syndromes (15.3%). Many other causes were identified in 33.3%. The overall survival rate was 68%. There was a significant difference on survival rates between the two periods (1996–2002 = 63.8% and 2003–2010 = 71.4%, 𝑃=0.04). Our study showed a myriad of non cardiac aetiologies for PPHN of the newborn, most of them related to lung disease or lung hypoplasia. We observed an improvement in survival rate since 2003, which was associated to the use of new therapies.